WORK CULTURE OF STATE CIVIL APPARATUS IN THE REGIONAL FOOD SERVICE OF NORTH SULAWESI PROVINCE - Mewengkang, Aswin L. W.; Tasik, Femmy C. M.; Kawung, Evelin J. R. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the work culture of the State Civil Apparatus (ASN) in the Regional Food Service of North Sulawesi Province. The research design used in this study uses qualitative research methods with a descriptive approach. This qualitative research method is used to examine the natural condition of the object. Data collection techniques consist of observation, interviews and documentation. According to the findings of the study, the work habits of state civil apparatus in the food service of North Sulawesi Province were influenced by office-hours-related discipline, seniority, and closeness to the leadership. In the pattern of work, the attitude of the State Civil Apparatus places itself as the person closest to the leadership, both direct and higher leadership, so that individual performance has an impact on the performance of agencies in providing public services. As part of the work culture, the State Civil Apparatus carries out its primary responsibilities and functions in accordance with regulations established by both the Ministry and the governor of North Sulawesi province regarding the implementation of work that must be carried out by the State Civil Apparatus. The values embraced in carrying out work as a state civil apparatus in the regional food service of the province of North Sulawesi as a whole are related to the regulations on the state civil apparatus that are based on law number 5 of 2014.